2017
DOI: 10.1002/adma.201700311
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Phase and Disorder Engineering in 1T‐MoSe2 Nanosheets for Enhanced Hydrogen‐Evolution Reaction

Abstract: MoSe is a promising earth-abundant electrocatalyst for the hydrogen-evolution reaction (HER), even though it has received much less attention among the layered dichalcogenide (MX ) materials than MoS so far. Here, a novel hydrothermal-synthesis strategy is presented to achieve simultaneous and synergistic modulation of crystal phase and disorder in partially crystallized 1T-MoSe nanosheets to dramatically enhance their HER catalytic activity. Careful structural characterization and defect characterization usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
266
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(294 citation statements)
references
References 70 publications
9
266
0
Order By: Relevance
“…[35,41,42] Notably,J 3 was the dominantv ibrational mode, indicating ar elatively higher proportion of 1T-MoSe 2 in the samples. [34,35] According to the area under the simulated peaks, the percentage of 1T phase in the MS-4, MS-6 and MS-8 samples was 56.4, 74.1 and6 7.7 %r espectively.T his indicated that the MS-6 sample possessedahigherc ontent of 1T phase than that of MS-4 and MS-8, which led to as hift of the d-orbital active center to al ower value. For each of the samples, there were two characteristic peaks corresponding to Mo 3d 3/2 (the higher energy peak) and the Mo 3d 5/2 (the lower energy peak).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[35,41,42] Notably,J 3 was the dominantv ibrational mode, indicating ar elatively higher proportion of 1T-MoSe 2 in the samples. [34,35] According to the area under the simulated peaks, the percentage of 1T phase in the MS-4, MS-6 and MS-8 samples was 56.4, 74.1 and6 7.7 %r espectively.T his indicated that the MS-6 sample possessedahigherc ontent of 1T phase than that of MS-4 and MS-8, which led to as hift of the d-orbital active center to al ower value. For each of the samples, there were two characteristic peaks corresponding to Mo 3d 3/2 (the higher energy peak) and the Mo 3d 5/2 (the lower energy peak).…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30] Previous studies have suggested that the HER performance of MoSe 2 is closely related to its crystalline structure and low-dimensional nanostructures.N otably, MoSe 2 has two active phases:c onventional 2H-MoSe 2 is aptype semiconductor with at rigonal prismatic lattice, displaying ar elativelyl ower intrinsic electrical conductivity andc atalytic efficiency,w hereas 1T-MoSe 2 with at rigonal lattice (octahedral coordination)e xhibits metallicp roperties and better HER performance. [34,35] The issues 2D transition metal dichalcogenide materials with layered nanostructures and specific phases usually exhibit excellent catalytic activitiesf or the hydrogen evolution reaction (HER).A facile solvothermal process was used to prepare ultrathin noble-metal-free 2D biphasic MoSe 2 nanosheets composed of am etastable metallic 1T phase and as emiconducting 2H phase. [34,35] The issues 2D transition metal dichalcogenide materials with layered nanostructures and specific phases usually exhibit excellent catalytic activitiesf or the hydrogen evolution reaction (HER).A facile solvothermal process was used to prepare ultrathin noble-metal-free 2D biphasic MoSe 2 nanosheets composed of am etastable metallic 1T phase and as emiconducting 2H phase.…”
Section: Introductionmentioning
confidence: 99%
“…Photoelectrochemistry is an ideal method for generating hydrogen because it uses solar energy and produces no pollutants in the process. [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] FeSe 2 is also a narrow bandgap semiconductor with a bandgap width of only 1.5 eV. [2][3][4][5][6] Photocatalyst can absorb solar energy to produce electron hole pairs, which can turn light energy into photoelectrochemical energy, while photogenerated electrons can split water to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Nevertheless,t he high cost and limited resources have seriously impeded their large-scale utilization. [8] TheM X 2 minerals exist in two phases (stable cubic pyrite-type and metastable orthorhombic marcasite-type) in nature,w here the subtle structural distinction can affect their binding ability of reaction intermediates,w hich thereby leads to different gains in catalytic performance. [6] So far, diverse strategies have been adopted to bring favorable interface and structural modulation on MX 2 for optimizing their electrocatalytic efficiencies.F or instance,e xfoliation of bulk materials into twodimensional (2D) ultrathin nanosheets can effectively increase the number of exposed active sites,t hus boosting the catalytic activity.…”
mentioning
confidence: 99%
“…[6] So far, diverse strategies have been adopted to bring favorable interface and structural modulation on MX 2 for optimizing their electrocatalytic efficiencies.F or instance,e xfoliation of bulk materials into twodimensional (2D) ultrathin nanosheets can effectively increase the number of exposed active sites,t hus boosting the catalytic activity. [8] TheM X 2 minerals exist in two phases (stable cubic pyrite-type and metastable orthorhombic marcasite-type) in nature,w here the subtle structural distinction can affect their binding ability of reaction intermediates,w hich thereby leads to different gains in catalytic performance. [8] TheM X 2 minerals exist in two phases (stable cubic pyrite-type and metastable orthorhombic marcasite-type) in nature,w here the subtle structural distinction can affect their binding ability of reaction intermediates,w hich thereby leads to different gains in catalytic performance.…”
mentioning
confidence: 99%